Role of adiponectin, resistin and monocyte chemo-attractant protein-1 in overweight/obese asthma phenotype in children - Abeer M. E. Osman; Ayat A. M. Motawie; Amany M. Abd Al-Aziz; Nadia A. A. Mostafa; Nehal S. Hasan; Mohamed S. El-Baz (BMC, 2023)
Abstract Background Asthma is a chronic inflammatory disorder of the airways with diverse overlapping pathologies and phenotypes contributing to a significant heterogeneity in clinical manifestations. Obesity may modify asthma risk, phenotype, and prognosis. A suggested mechanism linking obesity and asthma is through systemic inflammation. Adipokines secreted by adipose tissue were suggested to provide a link between obesity and asthma. Objective To have an understanding for the contribution of adiponectin, resistin and MCP-1 to development of distinct asthma phenotype in overweight/obese children through assessment of their serum level and correlation to pulmonary function tests. Subjects and methods The study included 29 normal weight asthmatics, 23 overweight/obese asthmatic children and 30 controls. All cases were subjected to detailed history taking, thorough examination and pulmonary function tests. Serum adiponectin, resistin, MCP-1 and IgE were assessed to all recruited subjects. Results Adiponectin level was significantly higher in overweight/obese asthmatics (24900 ± 1600 ng/ml) compared to normal weight asthmatics (21700 ± 1700 ng/ml) and control (23000 ± 3200 ng/ml), (p < 0.001 & 0.051 respectively). Normal weight asthmatics had significantly lower adiponectin level than control, (p = 0.039). A significant low level of MCP-1 in overweight/obese asthmatics (149.5 (20-545) ng/L) compared to control (175 (28 -1123.5) ng/L), p = 0.037. No significant difference was found regarding resistin. Normal weight asthmatics had significantly lower FEV1% and FVC% compared to overweight/obese asthmatics (p = 0.036, 0.016 respectively). A significant positive correlation was found between (FEV1%, FVC) and BMI in normal weight asthmatics (P = 0.01, < 0.01 respectively) and a significant negative correlation between PEF and BMI (-0.42, p = 0.05) in obese/overweight asthmatics. Resistin/adiponectin ratio was not affected by sex, degree of asthma severity or level of asthma control in either normal weight or overweight/obese asthmatic. Conclusion This work could suggest that adiponectin may play a role in overweight/obese asthma phenotype where it is possible to have a dual action (pro & anti- inflammatory). It seems that resistin had no role in asthma pathogenesis.